2023
DOI: 10.24976/discov.med.202335175.14
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Genetic Mutation Characteristics Based on Large Panel Next-Generation Sequencing (NGS) Detection in Multiple Primary Lung Cancers (MPLC) Patients

Abstract: Background: With the wide application of multislice spiral computed tomography (CT), the frequency of detection of multiple lung cancer is increasing. This study aimed to analyze gene mutations characteristics in multiple primary lung cancers (MPLC) using large panel next-generation sequencing (NGS) assays. Methods: Patients with MPLC surgically removed from the Affiliated Hospital of Guangdong Medical University from Jan 2020 to Dec 2021 enrolled the study. NGS sequencing of large panels of 425 tumor-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The mutation spectrum of our cohort was similar to that reported by a recent study which performed 425 panel sequencing of 114 lesions of MPLC. 42 We observed significantly higher mutational frequency of RBM10 and lower mutational frequencies of TP53, PIK3CA and STK11 in super MPLC than conventional LUAD, indicating the distinct molecular mechanisms underlying the pathogenesis of super MPLC. Previous studies showed that somatic mutations in specific oncogenes, including BRAF, NRAS and EGFR, were early genomic events for LUAD, 43 and the mutations of the oncogenes were also identified in the pre-invasive lesions of super MPLC, suggesting their important roles in the early pathogenesis.…”
Section: Discussionmentioning
confidence: 63%
“…The mutation spectrum of our cohort was similar to that reported by a recent study which performed 425 panel sequencing of 114 lesions of MPLC. 42 We observed significantly higher mutational frequency of RBM10 and lower mutational frequencies of TP53, PIK3CA and STK11 in super MPLC than conventional LUAD, indicating the distinct molecular mechanisms underlying the pathogenesis of super MPLC. Previous studies showed that somatic mutations in specific oncogenes, including BRAF, NRAS and EGFR, were early genomic events for LUAD, 43 and the mutations of the oncogenes were also identified in the pre-invasive lesions of super MPLC, suggesting their important roles in the early pathogenesis.…”
Section: Discussionmentioning
confidence: 63%